2021
DOI: 10.1186/s12958-021-00846-6
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related complications and perinatal outcomes following progesterone supplementation before 20 weeks of pregnancy in spontaneously achieved singleton pregnancies: a systematic review and meta-analysis

Abstract: Background Progesterone supplementation is widely performed in women with threatened miscarriage or a history of recurrent miscarriage; however, the effects of early progesterone supplementation on pregnancy-related complications and perinatal outcomes in later gestational weeks remain unknown. Methods Ovid MEDLINE, the Cochrane Library, Embase and ClinicalTrials.gov were searched until April 3rd, 2021. Randomized controlled trials regarding sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…As regard to progestogens, a proportion of 19.0% of women was exposed to progesterone during pregnancy, mainly concentrated in the 1 st TP (14.8%), probably in an attempt to prevent miscarriages. The use of progestogens, in particular in the prevention of non-recurrent miscarriage, is worthy of attention because its efficacy is still unsupported by conclusive evidence [ 42 , 43 ]. In 2009 the World Health Organization (WHO) recommended not to prescribe progestogens for preventing miscarriages.…”
Section: Discussionmentioning
confidence: 99%
“…As regard to progestogens, a proportion of 19.0% of women was exposed to progesterone during pregnancy, mainly concentrated in the 1 st TP (14.8%), probably in an attempt to prevent miscarriages. The use of progestogens, in particular in the prevention of non-recurrent miscarriage, is worthy of attention because its efficacy is still unsupported by conclusive evidence [ 42 , 43 ]. In 2009 the World Health Organization (WHO) recommended not to prescribe progestogens for preventing miscarriages.…”
Section: Discussionmentioning
confidence: 99%
“…Allowing for a higher concentration of serum P4 in P4-supplemented cKO mice compared to WT mice, the possibility that expression of CD161 on uNK cells in the spongiotrophoblast layer was mediated through a glucocorticoid receptor pathway. As clinical evidence, progesterone supplement was demonstrated to prevent miscarriage in women with recurrent miscarriage of unclear etiology [ 41 ] and protect the onset of HDP [ 42 ]. Recently, it was also reported that progesterone supplement therapy is clinically effective for the functional failure of the placenta with structural abnormalities [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…I 2 was used to evaluate heterogeneity, and values of 25, 50, and 75% were used for classification of low, moderate, and high heterogeneity, respectively ( Higgins et al, 2003 ). The meta-analysis was performed using a random-effects model that was weighted according to the sample size of studies ( Wu et al, 2021 ). A difference with a p value below 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%